Pengaruh Usia, Jenis Kelamin, dan Upah terhadap Produktivitas Karyawan dengan Pengalaman Kerja sebagai Variabel Moderasi (Studi Kasus pada Karyawan Bagian Produksi di PT Jaya Lestari Sejahtera) - Nurisa, Fadia; Yulia, Iis Anisa; Fitrianti, Dewi (Jurnal EMT KITA, 2025)
This study aims to examine the effect of age, gender, and wages on employee productivity, with work experience as a moderating variable. The sample consisted of all production employees at PT Jaya Lestari Sejahtera, totaling 120 respondents. A census sampling method was used, and the data were obtained from secondary sources provided by the company. Hypothesis testing was conducted using descriptive statistics, multiple linear regression, and moderation regression analysis. The results indicate that age and wages have a partial effect on employee productivity. Furthermore, work experience significantly moderates the relationship between age and productivity, as well as between wages and productivity.